2018
DOI: 10.1111/jsbm.12418
|View full text |Cite
|
Sign up to set email alerts
|

Task Conflict, Narcissism and Entrepreneurial Capability in Teams Planning a Business: A Moderated Moderation Approach to Explaining Business Planning Performance

Abstract: Drawing on the dynamic self‐regulatory processing model of narcissism, we hypothesize that in teams planning a business, task conflict relates positively to business planning performance and that this link is reinforced by the team's narcissism. By integrating aspects of human capital theory, this brighter side of narcissism is amplified where the narcissism is aligned with entrepreneurial capability and the team members' belief in their entrepreneurial capability. The findings of the moderated moderation anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 118 publications
(173 reference statements)
0
30
0
Order By: Relevance
“…This results in team members maintaining positive attitudes toward entrepreneurship, which can ultimately affect the team's entrepreneurial planning performance. Kollmann et al (2019) verified that the level of narcissism in entrepreneurial teams strengthened the positive correlation between task conflicts and business planning performance. Besides, they also found that the moderating role played by the team's level of narcissism is stronger when team member's actual and perceived entrepreneurial capabilities are higher.…”
Section: Narcissism and Entrepreneurial Performancementioning
confidence: 74%
See 2 more Smart Citations
“…This results in team members maintaining positive attitudes toward entrepreneurship, which can ultimately affect the team's entrepreneurial planning performance. Kollmann et al (2019) verified that the level of narcissism in entrepreneurial teams strengthened the positive correlation between task conflicts and business planning performance. Besides, they also found that the moderating role played by the team's level of narcissism is stronger when team member's actual and perceived entrepreneurial capabilities are higher.…”
Section: Narcissism and Entrepreneurial Performancementioning
confidence: 74%
“…For example, the meta-analysis of Jin et al (2017) found that the characteristics of entrepreneurial teams (e.g., team size, average team member experience, heterogeneity related to age, gender, and work experience) have a significantly positive impact on the performance of startups. The results of Kollmann et al (2019) illustrate that team task conflict can effectively improve the quality of business plans in student teams. De Mol et al (2015) analyzed 44 studies on entrepreneurial team cognition and demonstrated that it could promote information processing, opportunity recognition, decision-making efficiency, and team learning.…”
Section: Examining the Relationship Between Narcissism And Entrepreneurship At The Team Levelmentioning
confidence: 98%
See 1 more Smart Citation
“…Despite the value of reflexivity, the reflexivity demands placed on entrepreneurial teams are uniquely challenging (Forsstrom-Tuominen et al, 2019; Kollmann et al, 2019). Several scholars have demonstrated that it is normally hard for teams spontaneously reflecting on their conventional work styles and processes (Konradt et al, 2015).…”
Section: Team Reflexivitymentioning
confidence: 99%
“…Few studies pay attention to team process factors. Kollmann et al (2018) investigate the relationship between task conflict and entrepreneurial capability in teams planning a business. In this study, scholars find task conflict is beneficial to business planning performance.…”
Section: Introductionmentioning
confidence: 99%